The spatial organization of mesopedobionts community of sod pinewood soils on the arena of the river Dnepr - Жуков, О. В.; Кунах, О. М.; Новікова, В. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The role of the edaphic factors and spatial variables in structuration of mesopedobionts community of sod pinewood soils on the arena of the river Dnepr within natural reserve "Dneprovsko-Orelsky" has been investigated. The research range consists of 7 transects, and each is made of 15 sample points. The distance between numbers in range makes 3 m. In each point soil-zoological tests for the quantitative account of soil mesofauna have been made, the vegetation has been described, penetration resistance, density, humidity and temperature of soil have been measured and its fractional structure has been established. Mesopedobionts of sandy steppe on the arena of the river Dnepr have been established to be in extreme conditions that is reflected by low level of abundance and species riches of the community of soil mesofauna. Six principal components have been found to be significant predictors of the mesopedobionts community structure from which one concerns a category of vegetative factors, one – to a category of soil penetration resistance and five – edaphic factors. Spatial PCNM-variables have been revealed as being much more predictive for the description of mesopedobionts community structure than edaphic factors. Considerable component of edaphic variables variation also is spatially structured. Spatial PCNM-variables represent various hierarchical levels of the spatial organization of mesopedobints community. Broad-scale and to a lesser degree – medium-scale components reflect a variation of spatially structured factors of environment. Fine-scale component reflects neutral aspect of community structuration.